Answer:
(fоgоh)(x)=2x³+1
Explanation:
Function composition is an operation where two functions, say f(x) and g(x), a new function h(x)=(fоg)(x)=f(g(x)) is generated. In this operation, the function g is applied to the result of the function f. Hence, function f:X→Y and g:Y→Z are joined to form a new function h:X→Z
Given
![f(x)=x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5p755aebcssr4n0gjfilwyrkbcyb6dyb4y.png)
![g(x)=2x](https://img.qammunity.org/2020/formulas/mathematics/high-school/rf2o55q38duq3zqxf7fe08azwo11w04kyd.png)
![h(x)=x^(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/8y5bqf9x2qryrpre7heix472535gaiyijd.png)
(fоgоh)(x)=
![f(g(h(x)))](https://img.qammunity.org/2020/formulas/mathematics/high-school/6i5qqnupyi7rfyaf88wkle3gk65f4353cw.png)
=
![f(g(x^(3)))](https://img.qammunity.org/2020/formulas/mathematics/high-school/427urivsuxqg6vqamjw7mtr5xt5zmryhvi.png)
=
![f(2x^(3))](https://img.qammunity.org/2020/formulas/mathematics/high-school/9dsj5agycnipaqo96ykg5jl8sjazuluyw2.png)
=2x³+1